Perancangan dan Pembangunan Sistem Pelayanan Data Penduduk dengan Metode BPR (Business Process Reengineering) - Neng Mira Indri Anggraeni; Dudih Gustian; Erfina, Adhitia (Cakrawala Repositori IMWI, 2020)
Population data is data used for various purposes such as taxpayer services, insurance, health insurance and much more. The process of collecting population data, especially in the Takokak sub-district is still very slow and the data are often not in accordance with the conditions in the community. One of the concepts that can be applied in facilitating population and regional processing is to reengineer the Business Process Reengineering (BPR) business process. In designing the system needed an enterprise architecture model of management information systems in processing population data in order to minimize failure when implementing the system can run as needed. For modeling, UML is used and analysis using the BPR method helps in the process of designing the basic structure of data processing so that it can help the design and development of information systems. The system design carried out in the BPR work plan will be web-based population data processing.